Information System Model for Worker Welfare Management for the Firm in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The research aim study  information system model for worker welfare management for the firm in Thai supply chain and  an evaluation of the model . This research was purposive sampling method approach with a sampling of ten experts in the field of information system and supply chain. The obtained data are analysed using mean and standard deviation. The research result demonstrates the model consists of five elements namely main components, Supplier, The firm, Satisfaction and service, Customers . The results from ten experts have evaluated the model and commented that the developed model showed high suitability which mean  information system model for worker welfare management for the firm in Thai supply chain  can develop  information  system,